Functional Diagnostic and Therapeutic Nanoconstructs for Efficient Probing of Circulating Tumor Cells - ASSANHOU, Assogba Gabin (My University, 2018)
The circulation of tumor cells in peripheral blood is mostly recognized as a prerequisite for cancer progression or systemic invasion, and it correlates with the pivotal hallmark of malignancies known as metastasis. Multiple detection schemes for circulating tumor cells (CTCs) have emerged as the most discerning criteria for monitoring the outcome of anticancer therapy. Therefore, there has been a tremendous increase in the use of robust nanostructured platforms for observation of these mobile tumor cells through various simultaneous diagnosis and treatment regimens developed from conventional techniques. This review seeks to give detailed information about the nature of CTCs as well as techniques for exploiting specific biomarkers to help monitor cancer via detection, capturing, and analysis of unstable tumor cells. We will further discuss nanobased diagnostic interventions and novel platforms which have recently been developed from versatile nanomaterials such as polymer nanocomposites, metal organic frameworks, bioderived nanomaterials and other physically responsive particles with desirable intrinsic and external properties. Herein, we will also include in vivo nanotheranostic platforms which have received a lot of attention because of their enormous clinical potential. In all, this review sums up the general potential of key promising nanoinspired systems as well as other advanced strategies under research and those in clinical use.
Keywords: malignant cancer systemic invasion circulating tumor cells diagnostic interventions nanotheranostic platforms